Podological Analysis in Children with Neuromotor Disabilities - Roberto Tedeschi (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Pediatric patients with neuromotor disorders often present with a variety of podiatric conditions. Despite the use of treatments like orthotics and insoles, the effectiveness of these interventions in managing associated foot problems is not well understood.